THE IMPACT OF CORPORATE INCOME TAX AND TAX HOLIDAY POLICY ON DIRECT FOREIGN INVESTMENT IN INDONESIA - Nunung Nuryani,; Tumpal J.R. Sitinjak,; Zhafirah Lavinia, (International Journal of Social Science, 2022)
Foreign investment has an important influence on a country's economy, it is also considered to be more resilient to crises because investors generally have a long-term perspective when investing in a country. However, the economic crisis in Indonesia caused the inflow of foreign direct investment to experience a drastic decline which led to a slowdown in economic growth in Indonesia. To increase interest in foreign investment in Indonesia again, it is necessary to have an incentive policy in order to attract foreign investors. Therefore, this study aims to examine whether the corporate income tax rate set by the government and the tax holiday policy determine foreign direct investment. Based on purposive sampling, a sample of 38 foreign direct investment inflows from 1981-2018 was obtained. The results show that the corporate income tax rate has a significant negative effect on foreign direct investment, but the tax holiday is not proven to have an effect on foreign direct investment. The results of this study indicate that in determining tax rules and policies, especially corporate income tax rates, it is necessary to consider the interests of foreign investors in order to attract more foreign direct investment to Indonesia.